2015
DOI: 10.1039/c5cc05680b
|View full text |Cite
|
Sign up to set email alerts
|

Concise synthesis of (±)-Lingzhiol via epoxy-arene cyclization

Abstract: Concise synthesis of (±)-Lingzhiol has been achieved. The key reaction involves one-step construction of a 5/5/6/6 tetra-ring backbone of Lingzhiol via epoxy-arene cyclization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 18 publications
0
30
0
Order By: Relevance
“…[12] Because we could not convert ketone 26 into epoxide 28 through aC orey-Chaykovsky reaction, [13] we wanted to preparei tb ye poxidation of the corresponding alkene. Even though the Qin group had reported that this reaction was unsuccessful, [6] we found conditions that could promote this crucial olefination reaction. Although classical Wittig conditions-Ph 3 PCH 3 I( 1.2 equiv), NaH (2.5 equiv), THF,0 8C; Ph 3 PCH 3 Br (2.5 equiv), tBuOK (2.5 equiv), toluene, 100 8C; Ph 3 PCH 3 Br (1.2 equiv), nBuLi (1.5 equiv), THF, À10 8C-and aT akai-Lombardo methylenation reaction [14] did not give the desired product (exo-15), we eventually found that the use of about three equivalents of methyltriphenylphosphonium bromide and 2.83 equivalents of potassium tert-butoxide were essential, as was their use from freshly opened bottlesi nT HF.…”
Section: Resultsmentioning
confidence: 83%
See 4 more Smart Citations
“…[12] Because we could not convert ketone 26 into epoxide 28 through aC orey-Chaykovsky reaction, [13] we wanted to preparei tb ye poxidation of the corresponding alkene. Even though the Qin group had reported that this reaction was unsuccessful, [6] we found conditions that could promote this crucial olefination reaction. Although classical Wittig conditions-Ph 3 PCH 3 I( 1.2 equiv), NaH (2.5 equiv), THF,0 8C; Ph 3 PCH 3 Br (2.5 equiv), tBuOK (2.5 equiv), toluene, 100 8C; Ph 3 PCH 3 Br (1.2 equiv), nBuLi (1.5 equiv), THF, À10 8C-and aT akai-Lombardo methylenation reaction [14] did not give the desired product (exo-15), we eventually found that the use of about three equivalents of methyltriphenylphosphonium bromide and 2.83 equivalents of potassium tert-butoxide were essential, as was their use from freshly opened bottlesi nT HF.…”
Section: Resultsmentioning
confidence: 83%
“…Because we could directly produce exocyclic olefin exo-15 from aW ittig reaction, we could shorten the synthetic route to lingzhiol reported by Qin and co-workers,whichwas published while our work was underway. [6] Thus, the allylic oxidation of exo-15 with tBuOOH in the presence of selenium dioxide led to allylic alcohol 33 as as ingle diastereomer (Scheme 7). This step was followed by epoxidation with mCPBA to give spiro epoxide 16 in 79 %y ield.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations